Potencial genotóxico e citotóxico de óleos essenciais de plantas do Cerrado e Pantanal sul-mato-grossense - Silva, Marcelo Fontes da (2023)
Biological potentialities are much studied in medicinal plants, mainly in the treatment of cancer, in addition to being of paramount importance for public health issues. The objective of this study was to evaluate the potential, genotoxic and cytotoxic of plant species from the Cerrado and Pantanal of Mato Grosso do Sul, Brazil. In screening for antiproliferative activity by the SRB method, the essential oil of Matayba guianensis was the one that showed the best results against neoplastic cells B16- F10, MCF-7 and U251, in addition to showing cytotoxicity on normal cell lines. The neoplastic strain U251 was also inhibited against the tested essential oils of Endlicheria paniculata and Siparuna guianensis. The essential oil of E. paniculata showed cytotoxic activity in the normal 3T3 and HUVEC strains, as well as the essential oil of Cymbopogon citratus that showed activity only in these non-tumor strains. The oil of S. guianensis showed cytotoxic activity on B16 and U251 and the essential oil of M. guianensis showed the best results regarding the activity of total inhibition of growth after 48 h of exposure, with potent inhibition of the tumor lineage U251 and weakly on the lineage tumor cell MCF7, and the murine normal cell 3T3. The selectivity index was calculated from the ratio of the concentrations that inhibit 50% of cell growth between 3T3 and B16 showed that there was no selectivity of the four samples on the murine neoplastic lineage, indicating that the essential oils were not selective for the B16 lineage. Between HUVEC and MCF7 and U251, the essential oil of E. paniculata showed better results with selectivity for both breast carcinoma and human glioblastoma. As for the SMART mutagenicity test, the data found in the treatments made with the essential oils of C. citratus and S. guianensis indicated that they do not have toxic or mutagenic activity. Therefore, based on the results found, it was concluded that the essential oils of M. guianensis and S. guianensis presented bioactive compounds with a significant antitumor effect and a better result for selectivity for tumor cells, respectively. Therefore, they can be considered as potential anticancer agents with promising effects in the search for new drugs in antitumor therapy.